Dual role of histone variant H3.3B in spermatogenesis: positive regulation of piRNA transcription and implication in X-chromosome inactivation. Issue 13 (29th June 2022) - Fontaine, Emeline; Papin, Christophe; Martinez, Guillaume; Le Gras, Stéphanie; Nahed, Roland Abi; Héry, Patrick; Buchou, Thierry; Ouararhni, Khalid; Favier, Bertrand; Gautier, Thierry; Sabir, Jamal S M; Gerard, Matthieu; et al.
Abstract: The histone variant H3.3 is encoded by two distinct genes, H3f3a and H3f3b, exhibiting identical amino-acid sequence. H3.3 is required for spermatogenesis, but the molecular mechanism of its spermatogenic function remains obscure. Here, we have studied the role of each one of H3.3A and H3.3B proteins in spermatogenesis. We have generated transgenic conditional knock-out/knock-in (cKO/KI) epitope-tagged FLAG-FLAG-HA-H3.3B (H3.3B HA ) and FLAG-FLAG-HA-H3.3A (H3.3A HA ) mouse lines. We show that H3.3B, but not H3.3A, is required for spermatogenesis and male fertility. Analysis of the molecular mechanism unveils that the absence of H3.3B led to alterations in the meiotic/post-meiotic transition. Genome-wide RNA-seq reveals that the depletion of H3.3B in meiotic cells is associated with increased expression of the whole sex X and Y chromosomes as well as of both RLTR10B and RLTR10B2 retrotransposons. In contrast, the absence of H3.3B resulted in down-regulation of the expression of piRNA clusters. ChIP-seq experiments uncover that RLTR10B and RLTR10B2 retrotransposons, the whole sex chromosomes and the piRNA clusters are markedly enriched of H3.3. Taken together, our data dissect the molecular mechanism of H3.3B functions during spermatogenesis and demonstrate that H3.3B, depending on its chromatin localization, is involved in either up-regulation or down-regulation of expression of defined large chromatin regions.